Buried flexible pipes behaviour in unreinforced and reinforced soils under cyclic loading. Issue 2 (April 2019) - Elshesheny, A.; Mohamed, M.; Sheehan, T.
Abstract : In this research, large-scale fully instrumented laboratory tests were conducted to investigate the behaviour of flexible high-density polyethylene (HDPE) pipes, in unreinforced and geogrid-reinforced sand, subjected to incrementally increasing cyclic loading; for example, due to different vehicle capacities or load increase with passing time. Results illustrated that the deformation rate in the pipe and footing, the strain generation rate in the pipe and reinforcing layers are rapidly increased in the initial loading cycles, in particular during the first 300 cycles, and then the rate of change decreases significantly as more cycles are applied. In the unreinforced case, increasing the pipe burial depth significantly reduced the generated deformation and strain in the pipe; however, it has a situational effect on the footing settlement, where it increased after pipe burial depth to its diameter ratio ( H / D ) of 2.5. In reinforced cases, deformation and strain significantly reduced with the increase in pipe burial depth and number of reinforcing layers. Measurement of strain illustrated that strain generated in the lower reinforcing layer is always higher than that recorded in the upper one, regardless of pipe burial depth and value of applied load.